Las imágenes fotográficas de América Latina en O Cruzeiro Internacional - Casadei, Eliza Bachega [UNESP] (My University, 2014)
Assuming that photographic images involve a process of aestheticization of events that is related to the construction of social identities, organizing the sensible and promoting standards and norms of behavior, the aim of this article is to study how the identity of Latin America was represented in the magazine O Cruzeiro Internacional from a study of photo reports published in this journal. In this article, we will explore the editorial project of this publication and we will study how this project was materialized in specific photo reports. These photo reports engendered a number of stereotypes about Latin America, linked to the American way of life and its values of development and consumption.

Asumiendo que las imágenes participan de un proceso de estetización de los acontecimientos que se relaciona con la construcción de las identidades sociales, con la organización de lo sensible y con la promoción de las normas de comportamiento, el objetivo de este trabajo es estudiar cómo la identidad de América Latina estuvo representada en la revista O Cruzeiro Internacional a partir de un estudio de los foto reportajes publicados en esta revista. En este artículo, delimitaremos el proyecto editorial de la publicación y mostraremos cómo este proyecto se materializó en foto reportajes específicos. Es posible percibir que esas producciones engendran muchos estereotipos sobre América Latina, vinculados al american way of life y sus valores de desarrollo y consumo.
Photographic images of Latin America in O Cruzeiro International
Keywords: Photojournalism; O Cruzeiro Internacional; Latin America; Fotoperiodismo; O Cruzeiro Internacional; América Latina